Electrocardiographic changes and importance of repolarization changes in cases with acute pancreatitis - Mehmet SÖKMEN,; Mehmet Sait BUĞDACI,; Erkan ÖZTEKİN, (Turkish Journal of Gastroenterology, 2019)
-